2021
DOI: 10.1111/jfpe.13833
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of hydrogel temperature and concentration on tapioca xerogel formation

Abstract: This study was aimed to examine the assessment of temperature and concentration on tapioca hydrogel into xerogel formation during sessile drop drying. The processing conditions during gelatinization of tapioca flour had an impact on xerogel characteristics. Various concentrations (5, 7.5, and 10% [wt/vol]) of tapioca flour dispersion were heated at a temperature of 50, 55, 60, 65, 70, 75, 80, 85, 90, 95, and 100°C for developing tapioca xerogel. Pasting parameters and least gelation concentration were investig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 36 publications
1
7
0
Order By: Relevance
“…Hence it was found that 4% concentration, 90 °C resulted in crack-free flat xerogels, which is suited for shape transformation. Similar crack free xerogels were also obtained from tapioca flour by Stephen et al (2021a).…”
Section: Rice Xerogelsupporting
confidence: 70%
“…Hence it was found that 4% concentration, 90 °C resulted in crack-free flat xerogels, which is suited for shape transformation. Similar crack free xerogels were also obtained from tapioca flour by Stephen et al (2021a).…”
Section: Rice Xerogelsupporting
confidence: 70%
“…The concentration of wheat–barley blend ranging from 2%, 4%, 6%, 8%,10%, 12%, 14%, 16%, 18%, and 20% was used for determining Least gelation concentration (LGC) by using 10‐ml distilled water. Each suspension was gelatinized in a water bath for 1 h, then cooled down to room temperature and tested for LGC (Stephen et al., 2021).…”
Section: Methodsmentioning
confidence: 99%
“…The lower values of gelling concentration show that the potential of any given starch sample in forming gel is potentially higher. In the case of food formulations, the smaller values for LGC tend to be beneficial as a lesser amount of starch is needed for gelling [29]. The LGC shows an inversely proportional relationship with the gelling potential of any given sample.…”
Section: Least Gelation Concentrationmentioning
confidence: 99%